SP174 Antibody Lacks Specificity for NRAS Q61R and Cross-Reacts With HRAS and KRAS Q61R Mutant Proteins in Malignant Melanoma. Issue 1 (January 2018) - Felisiak-Goląbek, Anna; Inaguma, Shingo; Kowalik, Artur; Wasąg, Bartosz; Wang, Zeng-Feng; Zięba, Sebastian; Pięciak, Liliana; Ryś, Janusz; Kopczynski, Janusz; Sarlomo-Rikala, Maarit; Góźdź, Stanislaw; Lasota, Jerzy; et al.
Abstract : HRAS, KRAS, and NRAS, highly homologous proteins, are often mutationally activated in cancer. Usually, mutations cluster in codons 12, 13, and 61 and are detected by molecular genetic testing of tumor DNA. Recently, immunohistochemistry with SP174 antibody has been introduced to detect NRAS Q61R-mutant protein. Studies on malignant melanomas showed that such an approach could be a viable alternative to molecular genetic testing. This investigation was undertaken to evaluate the value of SP174 immunohistochemistry for detection of NRAS Q61R-mutant isoform. Two hundred ninety-two malignant melanomas were evaluated using Leica Bond-Max automated immunostainer. Twenty-nine tumors (10%) showed positive immunoreactivity. NRAS codon 61 was polymerase chain reaction amplified and sequenced in 24 positive and 92 negative cases using Sanger sequencing, quantitative polymerase chain reaction, and next-generation sequencing approaches. A c.182A>G substitution leading to NRAS Q61R mutation was identified in 22 tumors. Two NRAS wild-type tumors revealed c.182A>G substitutions in H RAS and KRAS codon 61, respectively. Both mutations were detected by next-generation sequencing and independently confirmed by Sanger sequencing. None of 85 NRAS codon 61 wild-type tumors and 7 NRAS mutants other than Q61R showed immunoreactivity with SP174 antibody. Thus, SP174 antibody was 100% sensitive in detecting NRAS Q61R-mutant isoform in malignant melanoma, but not fully specific as it cross-reacted with HRAS and KRAS Q61R-mutant proteins. Therefore, molecular testing is needed to determine which RAS gene is mutated. The rarity of HRAS and KRAS Q61R mutants in malignant melanoma let previous investigations erroneously conclude that SP174 is specific for NRAS Q61R-mutant protein. Abstract : Supplemental Digital Content is available in the text.